Dietary Intake, Lifestyle Factors, and Metabolic Risk: Insights from Health Check-Ups at a Private Healthcare Facility in Coimbatore, India - Shanthi Dhandapani; Kamar Afshan; Sesham Shreya; Catherine Lily Vincy; V. Yuvaraj; V. Krithika (Amerta Nutrition)
Background: Over the last decade (2014–2024), the global prevalence of metabolic risk factors such as dyslipidemia (5-8%), hypertension (5-10%), obesity (10-15%) and elevated blood glucose levels (10-15%) has been steadily increasing.